Plautus' Aulularia, Držić's Assembly, Moliere’s and Jovan Sterija Popović’s The Miser – the comparative key to four comedies - Sovrlić, Aleksandra N. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
In this paper, we look at three major comedies in a comparative vein: The Miser by Jovan Sterija Popović from the 19th century, The Miser by Jean Baptiste Poquelin Molière from the 17th century, and The Assembly by Marin Držić from the 16th century. However, we are aware of the fact that the study of these three works would not be complete without insight into their common template, which is the comedy Aulularia, produced in the second century AD by Tito Maccius Plautus, which, as we know, was the originator for the creation of the aforementioned works. Therefore, we will strive, first of all, to present Plautus’ comedy, as well as the context in which it was produced, what novelties it brought to the world of literature, what models Plautus himself followed, what he took from the Greek tradition, and what he introduced as new. Then, we will apply this procedure to the three comediographic works by Jovan Sterija Popović, Molière, and Marin Držić. In doing so, we will pay particular attention to those qualities that distinguish these writers first in their literary milieu and then in comparison to each other.
Keywords: Plautus; Aulularia; Marin Držić; Assembly; Molière; Jovan Sterija Popović; The Miser